Gravity and lymphodynamics. Issue 10 (19th May 2022) - Holm‐Weber, Thomas; Kristensen, Rasmus Eskild; Mohanakumar, Sheyanth; Hjortdal, Vibeke E.
Abstract: The lymphatic system is compromised in different groups of patients. To recognize pathology, we must know what is healthy. We use Near‐Infrared Fluorescence (NIRF) to assess peripheral lymphatic function in humans. We have shown that external factors such as exercise, hyperthermia, and pharmacological mediators influence the function of peripheral lymphatic vessels. In this study, we explored the impact on lymphatic vessels by the ever‐present external factor— gravity . We used NIRF imaging to investigate the lymphatic changes to gravity. Gravity was assessed by changing body position from supine to standing. We extracted following lymphatic functional parameters: lymphatic packet propulsion frequency (contractions/min), velocity (cm/s), and pressure (mmHg). Raw data analysis was performed using a custom‐written Labview program. All sequences were analyzed by two observers and interclass correlation scores were calculated. All statistical analysis was performed using RStudio Team (2021). RStudio: Integrated Development Environment for R. RStudio, PBC. Healthy participants ( n = 17, 11 males, age 28.1 ± 2.6 years) were included. The lymphatic packet propulsion frequency at baseline was 0.5 ± 0.2 contractions/min and rose within 3 min significantly to a maximum of 1.2 ± 0.5 contractions/min during upright posture and remained significantly higher than the baseline lymphatic packet propulsion frequency after lying down again for up to 6 min. The lymph velocity was 1.5 ± 0.4 cm/s at baseline and changed in both directions and without a specific pattern at different points in time during standing. Lymph pressure was significantly higher while standing (mean increase 9 mmHg, CI: 2–15 mmHg). The ICC scores were 89.8% (85.9%–92.7%), 59.3% (46.6%–69.6%) and 89.4% (79.0%–94.8%) in lymphatic packet propulsion frequency (130 observations), velocity (125 observations), and pressure (30 observations), respectively. The lymphatic system responds within few minutes to gravitational changes by increasing lymphatic packet propulsion frequency and pressure. Abstract : Gravity affects our Lymphatic system. This study showed the lymphatic response to gravity.